Problems of accessing scholarly publications by Nigerian scientists: a study of the university of Ibadan (2003)
"This study assesses the impact of information technology on scholarly publications and the problem associated with accessing the publications by scientists at the University of Ibadan, Nigeria. The study discovered that ICT facilities like the Internet and e-mail have taken root in the academic environment through providing access to scholarly publications. However, the implementation of IT application is still a problem to Nigerian academics because of many factors, ranging from the lack of funds to fluctuations in the suppIy of electricity. This has indirectly affected the level of usage of ICT in Nigeria by the lecturers and it has hindered access to scholarly publications useful for research. Despite many constraints, the use of information technology is growing among Lecturers in Nigerian universities"